Inspection control in the field of environmental protection - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The Republic of Serbia has built an extensive and comprehensive system of inspection control in the field of environmental protection. Through the specialization on various environmental issues in different areas of social life it is provided the comprahensiveness of inspection control, and through the establishing a wide network of environmental inspection services, it is created a fundamental prerequisite for the good functioning of the inspection in the field of environmental protection. The current organization of inspection services, however, represents only the initial legal basis, which should be further improved, for the possibility of effective exercise of the inspection in this area of ??social life. First of all, it should be  made a detailed codification of legal rules on inspection control, by adoption a general law on inspection control, and then pass a special law on inspection control in the field of environmental protection, by which it would be introduced all standards set by Recommendation of the European Parliament and the Council of 4 April 2001 providing for minimum criteria for environmental inspections in the Member States.